2,5-Diketopiperazines From a Sponge-Derived Fungus Aspergillus sclerotiorum - Wang, Chao-Yi; Liu, Xiao-Han; Zheng, Yao-Yao; Ning, Xing-Yan; Zhang, Ya-Hui; Fu, Xiu-Mei; Li, Xin; Shao, Chang-Lun; Wang, Chang-Yun (Frontiers in Microbiology, 2022)
Three new 2,5-diketopiperazines, speramide C (1), 3,21-epi-taichunamide F (2) and 2-epi-amoenamide C (3), along with four known analogs (4−7), were obtained from the sponge-derived fungus Aspergillus sclerotiorum GDST-2013-0501 collected from the South China Sea. The chemical structures of new compounds were elucidated by analyzing NMR and MS spectroscopy data, and their absolute configurations were determined by electronic circular dichroism (ECD) calculations. Compound 1 represents the first prenylated indole alkaloid with ethylene oxide ring at the isopentenyl side chain. Compound 4 displayed DNA topoisomerase I inhibitory activity and antibacterial activity against Stapyhloccocus epidermidis. The low cytotoxic or non-cytotoxic compound 4 displayed DNA topoisomerase I inhibitory activity, which could provide a starting point for the development of antitumor agents.